Prone lachman with ultrasound: A literature review and description of the technique - Raja, A. E.; Meyer, R.; Tunis, B. G.; Moreland, M. L.; Tunis, J. G. (Current Sports Medicine Reports, 2022)
Magnetic resonance imaging is the current gold standard imaging modality for diagnosing anterior cruciate ligament (ACL) tears. However, ultrasound has grown in popularity for detecting ACL injuries because of its low cost, portability, and dynamic assessment capabilities. Recent studies demonstrate high sensitivity and specificity for diagnosing isolated ACL tears via ultrasound, but tremendous heterogeneity remains for optimal technique including patient positioning, transducer placement, and dynamic versus static ultrasound usage. As ultrasound becomes ubiquitous in clinics, training rooms, and on the sidelines, identifying objective and sensitive measurements to appropriately screen athletes for significant knee injuries is imperative. This article aims to review the current role of diagnostic ultrasound in ACL injuries and propose a standardized version of the Prone Lachman with Ultrasound test, which is an objective, reliable, and easily reproducible technique to evaluate ACL competency. Developing a standardized protocol will expand the use of point-of-care ultrasound, which may reduce cost and improve efficiency in care.